2013
DOI: 10.11564/20-1-386
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Home Environment and Adolescent Sexual Behaviour in Southwestern Nigeria

Abstract: This study examines adolescent sexual behaviour within the context of the home environment (urban low, medium and high residential density)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Specifically, adolescents who were raised in urban areas were reported to be better informed about safe sex. A similar finding was reported by Adeboyejo and Onyeonoru [ 27 ] in their study of adolescents´ sexual behaviours in South-west Nigeria. They concluded that urbanites are better exposed to technologies and other materials to learn about contraceptives like condoms.…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, adolescents who were raised in urban areas were reported to be better informed about safe sex. A similar finding was reported by Adeboyejo and Onyeonoru [ 27 ] in their study of adolescents´ sexual behaviours in South-west Nigeria. They concluded that urbanites are better exposed to technologies and other materials to learn about contraceptives like condoms.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Fordham & Ogbu (1986) among adolescents in the US found that most adolescents preferred popularity and acceptance in the peer group over schooling, suggesting that where peer perceptions are not supportive to good schooling outcomes, peers did not maximize opportunities that increased their schooling. A previous study by Harding (2003) also found that neighbourhoods influence schooling outcomes through age at sexual debut and teenage pregnancy, which is consistent with another study which found that teenagers in low socioeconomic neighbourhoods had sexual debut at a young age (Burgard & Lee-Rife 2009;Adeboyejo & Onyeonoru, 2003), become teenage mothers and dropout out of school (Crane 1991).…”
Section: Literature Reviewsupporting
confidence: 84%
“…Children are educated and molded after what is obtained in the family. Many facets of the family have great impact on the children, adolescents included (Orluwene, Ekechuwku, & Ojiugo, 2015) In the adolescent years, the informal context of home environment provides a framework (whether smoothening or constraining) which structures behavior, perhaps in different ways from the formal contexts of the school and influence of groups and associations in the wider environment (Adeboyejo, & Onyeonoru, 2002). Information on household composition is critical for understanding family size in relation to age and sex distribution, educational status, employment status and wealth quintile because it is a determinant of health status and wellbeing.…”
Section: Home Background and Risky Sexual Behaviormentioning
confidence: 99%